2022
DOI: 10.3389/fimmu.2022.833040
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis Vesicles Induce Mitochondrial Apoptosis by Regulating miR96-5p/Abca1 to Inhibit Osteoclastogenesis and Bone Loss

Abstract: Bone loss due to an increased osteoclast activity is common in osteoporosis and rheumatoid arthritis. For the first time, we observed an inhibition of osteoclast formation and bone resorption by outer-membrane vesicles (OMVs) from a Gram-negative, pathogenic bacterium, Proteus mirabilis (P.M). Gene ontogeny and KEGG enrichment analyses of miRNA and mRNA sequencing data demonstrated a significant effect of P.M OMVs on mitochondrial functions and apoptotic pathways. OMVs induced mitochondrial dysfunction through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“… 196 Reduced miR-96-5p expression in osteoclasts mediates the regulation of ATP binding cassette subfamily A member 1 (Abca1), contributing to an increased level of mitochondria-dependent apoptosis in vitro and attenuated arthritic bone loss in vivo. 197 …”
Section: Deregulated Mirnas In Ramentioning
confidence: 99%
See 1 more Smart Citation
“… 196 Reduced miR-96-5p expression in osteoclasts mediates the regulation of ATP binding cassette subfamily A member 1 (Abca1), contributing to an increased level of mitochondria-dependent apoptosis in vitro and attenuated arthritic bone loss in vivo. 197 …”
Section: Deregulated Mirnas In Ramentioning
confidence: 99%
“…196 Reduced miR-96-5p expression in osteoclasts mediates the regulation of ATP binding cassette subfamily A member 1 (Abca1), contributing to an increased level of mitochondria-dependent apoptosis in vitro and attenuated arthritic bone loss in vivo. 197 During osteoclast differentiation, miR-146a hinders osteoclast progenitor differentiation through a marked decrease in Relb transcript levels. Targeted delivery of miR-146a into Ly6C high monocytes was shown to effectively repress monocyte-toosteoclast conversion and prevent joint destruction in CIA mice.…”
Section: Deregulated Mirnas In Ramentioning
confidence: 99%
“…We further performed a correlation analysis between the bacterial genera and bone phenotypes and found that various bacterial genera were positively or negatively correlated with BV/TV (|r| > 0.5), including Proteus , Erysipelatoclostridium , Akkermansia , and Roseburia . Proteus , a gram-negative pathogenic bacterium, contributes to the inhibition of osteoclast formation and bone resorption by its outer-membrane vesicles ( Wang et al., 2022 ). Erysipelatoclostridium , which was found to be linked to BMD at multiple sites, has been reported to produce acetate, which is a short-chain fatty acid that inhibits inflammatory Th17 cell activation and promotes Treg cell differentiation ( Zhang et al., 2016 ; Cao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the gut microbiota are reported to be associated with vaccine immunogenicity and adverse events [ 6 ], suggesting that vaccination-induced changes in our microbiota composition could also have an impact on our overall health. Interestingly, outer-membrane vesicles (OMV) derived from bacteria can be used as vaccines to prevent infections [ 7 ], as well as to protect against bone loss [ 8 ]. Genetic engineering technology is being used to improve and expand the usefulness of such OMV vaccines by reducing toxicity and, in expressing the crucial antigens, multiple antigenic variants and heterologous antigens.…”
Section: Infectious Diseasesmentioning
confidence: 99%